MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR MURID PADA MUATAN IPAS MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING DI KELAS III SDN MELAYU 2 BANJARMASIN - Rusmansyah; Ilham, Muhammad; Fauzan Lavionda Arsyad, Muhammad; Nur Azizah, Wafa; Hasanah, Nidaul; Mahmudah, Nadia; Ruspina Putri, Nanda; Ruhama, Siti; Sahryda; Almayanti Yedida, Yetri; Yulianti, Vina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low levels of critical thinking skills and learning outcomes among third-grade students in the IPAS subject at SDN Melayu 2 Banjarmasin. The purpose of this study was to describe student activities, improvements in critical thinking skills, and student learning outcomes through the implementation of the Problem-Based Learning model. This study employed a Classroom Action Research (CAR) design conducted over four sessions. The research subjects were 17 students in third-grade class B at SDN Melayu 2 Banjarmasin. Data analysis was conducted using descriptive qualitative and quantitative methods by comparing the results across each session. The results showed that student activity increased from 38% in session 1 to 82% in session 4. Students’ critical thinking skills also improved from 39% (meeting the “Some Students Proficient” criterion) to 82% (meeting the “Almost All Students Proficient” criterion). Student learning outcomes improved: cognitive mastery increased from 40% to 82%, affective mastery increased from 42% to 88%, and psychomotor mastery increased from 38% to 88%. Based on these results, it can be concluded that the implementation of the Problem-Based Learning model can improve learning activities, critical thinking skills, and learning outcomes in IPAS for third-grade students at SDN Melayu 2 Banjarmasin.